PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 230 PALEMBANG - Ratih Fitriyah; Destiniar, Destiniar; Nurlela, Nurlela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the fact that the learning carried out is still conventional and too teacher-centred, so this causes students' science learning outcomes to be in the low category. The aim of this research was to determine the effect of the talking stick learning model on the science learning outcomes of class V students at SD Negeri 230 Palembang. This research is quantitative using a pre-experimental type experimental method with a one group pretest-posttest design.The research population consisted of 29 fifth grade students at SD Negeri 230 Palembang. The data analysis technique used in the prerequisite test is the normality test and hypothesis test (t-test) with the paired sample t test. Based on the results of data analysis using the t-test, a significance value of 0.000 < 0.05 was obtained, in this case it means that H0 is rejected and Ha is accepted, which means that there is a significant influence in the use of the talking stick learning model ont he science learning outcomes of class V students at SD Negeri 230 Palembang.